Does financial deleveraging affect governments' desirability of privatization? Evidence from the Chinese listed local SOEs - Weiwei Yang; He Wang; Xie Huobao (Journal of Applied Economics, 2023)
The rapid growth of local SOEs in China largely depends on high leverage, thus local governments and their SOEs will face harder budget constraints when the central bank implements tight credit policies. Using a sample of listed local SOEs in the Chinese A-share market, this paper attempts to investigate the relationship between financial deleveraging and privatization of local SOEs. We find that privatization of the Chinese local SOEs increases significantly during financial deleveraging, and this effect is more pronounced among SOEs with less tax contribution, fewer employees and that cause greater financial burden to the local governments. This paper broadens the research on environmental factors that drive politicians to privatize.
Keywords: 330; Financial deleveraging; local state-owned enterprises; privatization